Cr ohmic contact on an Ar+ ion modified 6H-SiC(0001) surface - Grodzicki, Miłosz; Chrzanowski, Jan; Mazur, Piotr; Zuber, Stefan; Ciszewski, Antoni (Oficyna Wydawnicza Politechniki Wrocławskiej, 2009)
Chromium layers were vapor deposited under ultrahigh vacuum onto samples cut out of a single crystal of 6H-SiC(0001) that were Ar+ bombardment modified. The substrates and electrical contacts formed by the Cr adlayer were characterized in situ by current-sensing atomic force microscopy (CS-AFM) and X-ray photoelectron spectroscopy (XPS). Cr/SiC contacts reveal a good I–V characteristic linearity without the use of heavy impurity doping and high-temperature annealing.
Optica Applicata, Vol. 39, 2009, nr 4, s. 765-772
Keywords: optyka; silicon carbide; chromium; electric contacts; AFM